Dealer Group or Financial Planning Group? A Brief Technical Note - Lujer Santacruz (Australasian Accounting, Business and Finance Journal, 2011)
This technical note examines whether the industry practice of using the term dealer group when referring to a financial planning group contributes to the general perception that financial advisers are not objective when making financial product recommendations. An experimental design carried out through an online survey is used. This is supplemented by a direct comparison survey on the two terminologies. The results provide a case for the industry to adopt a new terminology.
Keywords: Financial planning